2017
DOI: 10.1155/2017/1682393
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulated Glycolytic Pathway Is Able to Maintain ATP Levels and Kinetic Patterns of Bovine Epididymal Sperm Subjected to Mitochondrial Uncoupling

Abstract: Studies have reported the importance of mitochondria in sperm functionality. However, for some species, the glycolytic pathway appears to be as important as oxidative phosphorylation in ATP synthesis and sperm kinetics. These mechanisms have not been fully elucidated for bovine spermatozoa. Therefore, the aim of this study was to evaluate the role of mitochondria and the glycolytic pathway in ATP synthesis, sperm movement patterns, and oxidative homeostasis of epididymal spermatozoa in bovine specimens. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 29 publications
5
37
0
4
Order By: Relevance
“…This finding suggested that glycolysis is more relevant than oxidative phosphorylation in the energetic metabolism of murine sperm. In a recent study conducted by our group, we observed similar results in bovine epididymal spermatozoa subjected to mitochondrial uncoupling and glycolysis stimulation (Losano et al, 2017a; Fig. 1).…”
Section: Role Of Mitochondria In Atp Production and Sperm Physiologysupporting
confidence: 83%
“…This finding suggested that glycolysis is more relevant than oxidative phosphorylation in the energetic metabolism of murine sperm. In a recent study conducted by our group, we observed similar results in bovine epididymal spermatozoa subjected to mitochondrial uncoupling and glycolysis stimulation (Losano et al, 2017a; Fig. 1).…”
Section: Role Of Mitochondria In Atp Production and Sperm Physiologysupporting
confidence: 83%
“…The sperm flagellum is powered by ATP produced by a complex of mitochondrial enzyme systems including the electron transport chain (ETC). As such, the powerhouse of the cell, the mitochondrion, is likely the foundation of sperm pathophysiology and structure (Darr, Cortopassi, Datta, Varner, & Meyers, ; Hu et al., ; Losano et al., ). Species differences in energy requirements for mitochondria for optimal sperm function are becoming evident, and individually tailored sperm handling and storage techniques (Darr, Varner et al., ; Davila et al., ; Gibb, Lambourne, Quadrelli, Smith, & Aitken, ) are likely to become clinical reality as the biochemistry and cellular physiology of sperm are uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the low glycolytic activity argues for a substantial utilisation of oxphos, glycolysis is also discussed as being essential to supply energy to sperm regions far from mitochondria to support motility 7 . For example, inhibiting oxphos while stimulating glycolysis maintained full sperm motility 36 . Other studies suggest that diffusion of ATP in sperm flagella is enough, if there is enough ATP stored in the tail, as it is the case in bull sperm 37 .…”
Section: Discussionmentioning
confidence: 99%